The Effect of Dart Board Media in Discovery Learning Model toward The Motivation Learning - Nita Aryuni; Army Auliah; Alimin Alimin (Universitas Negeri Medan, 2024)
This quasy-experimental research aims to determine the effect of Dart Board media in the Discovery Learning Model toward the motivation learning. The research design used was pretest - posttest control group design. The population in this study were students of class XI SMA Negeri 1 Soppeng who studied chemistry totaling three classes. Sampling used was simple random technique so as to obtain class XI 9 as an experimental group and class XI 10 as a control group. Data collection was done by giving motivation questionnaire at the beginning and end of the meeting. The results of descriptive statistical analysis obtained the average learning motivation value of the experimental group pretest of 73,5 and posttest of 80,83, and the control group pretest of 73,90 and posttest of 77,25. The results of the inferential statistical analysis at a significant level of 0,05 obtained Zcount> Ztable (2,62 > 0,65), then H1 is accepted and H0 is rejected. Based on the test results it can be concluded that there is effect of Dart Board media in the Discovery Learning Model toward the motivation learning.